2004
DOI: 10.1007/s00464-003-8513-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a virtual reality upper gastrointestinal simulator and cross validation using structured assessment of individual performance with video playback

Abstract: The upper gastrointestinal simulator may be a useful tool for determining whether a trainee has achieved a desired level of competence in endoscopy. The next step will be to validate the VES score in real procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This research suggests that exposing trainees to simulators in the beginning of their training may accelerate initial skills acquisition in addition to improving confidence in completing procedures early on, but does not necessarily correlate to long‐term outcomes of training. Simulation is currently being used in adult endoscopy, and studies have shown reliability in measuring skill acquisition …”
Section: Discussionmentioning
confidence: 99%
“…This research suggests that exposing trainees to simulators in the beginning of their training may accelerate initial skills acquisition in addition to improving confidence in completing procedures early on, but does not necessarily correlate to long‐term outcomes of training. Simulation is currently being used in adult endoscopy, and studies have shown reliability in measuring skill acquisition …”
Section: Discussionmentioning
confidence: 99%
“…Similar studies on assessment tools have been performed by assessing videotaped performance of procedural skills after masking the identity of the trainees or by employing assessors not known to the trainees and vice versa. [11121819] We were not able to arrange this methodology because of lack of funds. Efforts were made to reduce this bias by the inclusion of residents who were not rotating with either of the two assessors at the time of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of a tool is its ability to assess skills consistently by different assessors at different times while construct validity is the ability of the tool to differentiate among varying levels of expertise. [67111213]…”
Section: Introductionmentioning
confidence: 99%
“…A recent study comparing clinical training alone to simulator training revealed that adopting a combined training approach is the best method to learn diagnostic EGD [ 20 ]. Studies describing simulator-based training for EGD are few compared to those reporting on colonoscopy or therapeutic endoscopy [ 19 , 21 , 22 ]. Existing literature suggests that simulator training can reduce the overall procedure time and significantly improve technical accuracy.…”
Section: Teaching Aidsmentioning
confidence: 99%